Mammals from the Allen Formation, Late Cretaceous, Argentina - Rougier, Guillermo Walter (2009)
A mammalian fauna from the Late Cretaceous locality of “Cerro Tortuga,” Allen Formation, Río Negro Province, Argentina, is described here based on a sample, represented by 7 isolated teeth which shows similarities with those reported from the Late Cretaceous Los Alamitos Formation. These two mammalian faunas largely agree on their overall composition at the supraspecific level but new species are recognized for some of the specimens described. Small-sized dryolestoids, mesungulatids and ferugliotheriids are present in Cerro Tortuga. A new species of Mesungulatum, [Bonaparte, J.F., Soria, M.F., 1985. Nota sobre el primer mamífero del Cretácico Argentino, Campaniano-Maastrichtiano, (Condylarthra). Ameghiniana 21, 177–183] leads to a reassessment of mesungulatid diversity in the Late Cretaceous South American mammalian faunas and some provisional considerations on the relative age of the mammal-bearing units. The South American Late Cretaceous radiation of dryolestoids has its origins in the early Late Cretaceous, at the latest, and extends into the Paleocene when their last remnants are obliterated possibly in relation to the incoming Laurasian tribosphenic mammals. The Late Cretaceous non-tribosphenic mammals have no clear link with the Jurassic and Early Cretaceous South American mammals, emphasizing the distinctiveness and episodic nature of the Mesozoic South American mammalian assemblages. The scant number of fossils and geochronologically discontinuous record may artificially accentuate the distinctiveness of the as yet poorly known pre-Late Cretaceous South American mammals, in particular if an epiric sea separated South Amerca into northen and southern realms.